MENDORONG LOYALITAS PELANGGAN DENGAN ANALISIS KERAGAMAN PRODUK, PERSEPSI HARGA DAN LOKASI TOKO - Dwijayani, Henny; Yeresti, Intan (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Competition in the tight business world forces retailers and shops to engage in marketing strategies that can improve their business objectives. One important factor in marketing is customer loyalty, which can be improved by some of the strategies covered in the marketing mix. The purpose of this study is to analyze some marketing mix to improve customer loyalty. This study uses descriptive and quantitative method, with a sample of 128 consumers in the shop Srikandi Ngawi. The sample was taken based on some criterion desired by the researcher. Data types are secondary data to be tested with descriptive and inferential statistics. T and F statistic test results MRA or multiple regression analysis, known variable product diversity and price perception affect customer loyalty but store location is not significant. Findings suggesting store locations are insignificant because the customer in principle does not take into account t he location if they wish to purchase.